Comparison of Problem-Based Learning and Discovery Learning Models in Improving Students’ Reading Comprehension at SMPN 2 Lampasio - Nur Suci Annisa; Hidayati; Indah Indrawati (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This research aimed to determine whether there is a significant difference between Problem-Based Learning and Discovery Learning models in improving students reading comprehension at the eighth-grade students of SMPN 2 Lampasio. This research is a type of quantitative research. The method used in this research is experiments with a comparative approach. The sampling technique employed in this research is “Total Sampling”, which involves including all eighth-grade students at SMPN 2 Lampasio. The data obtained from a test. The researcher used the IBM SPSS to analyze the data. The results showed that the average pre-test of the students in the Problem-Based Learning was 45.15, and the post-test results showed an average score of 78.85. Meanwhile, the students in the Discovery Learning class had an average pre-test score of 39.80 and a post-test score of 73.55. Based on the average pre-test and post-test scores, there is an improvement in the students' learning outcomes in reading descriptive texts after being given the treatment using the Problem-Based Learning and Discovery Learning models. The hypothesis test by using SPSS conducted on the post-test results of the Problem-Based Learning and Discovery Learning classes showed a significance value of 0.004<0.05 (sig.<α), so it is stated that the Ho hypothesis is rejected and Ha is accepted. It could be concluded that there is a significant difference in improving the students’ reading comprehension between using the Problem-Based Learning model and the Discovery Learning model in the eighth-grade student of SMPN 2 Lampasio.